Eicosapentaenoic acid induces DNA demethylation in carcinoma cells through a TET1‐dependent mechanism. Issue 11 (14th May 2018) - Ceccarelli, Veronica; Valentini, Virginia; Ronchetti, Simona; Cannarile, Lorenza; Billi, Monia; Riccardi, Carlo; Ottini, Laura; Talesa, Vincenzo Nicola; Grignani, Francesco; Vecchini, Alba
ABSTRACT: In cancer cells, global genomic hypomethylation is found together with localized hypermethylation of CpG islands within the promoters and regulatory regions of silenced tumor suppressor genes. Demethylating agents may reverse hypermethylation, thus promoting gene re‐expression. Unfortunately, demethylating strategies are not efficient in solid tumor cells. DNA demethylation is mediated by ten‐eleven translocation (TET) enzymes. They sequentially convert 5‐methylcytosine (5mC) to 5‐hydroxymethylcytosine (5hmC), which is associated with active transcription; 5‐formylcytosine; and finally, 5‐carboxylcytosine. Although α‐linolenic acid, eicosapentaenoic acid (EPA), and docosahexaenoic acid, the major n‐3 polyunsaturated fatty acids, have anti‐cancer effects, their action, as DNA‐demethylating agents, has never been investigated in solid tumor cells. Here, we report that EPA demethylates DNA in hepatocarcinoma cells. EPA rapidly increases 5hmC on DNA, inducing p21 Waf1/Cip1 gene expression, which slows cancer cell‐cycle progression. We show that the underlying molecular mechanism involves TET1. EPA si multaneously binds peroxisome proliferator‐activated receptor γ (PPARγ) and retinoid X receptor α (RXRα), thus promoting their heterodimer and inducing a PPARγ‐TET1 interaction. They generate a TET1‐PPARγ‐RXRα pro tein complex, which binds to a hypermethylated CpG island on the p21 gene, where TET1 converts 5mC to 5hmC. In an apparent shuttling motion, PPARγ and RXRα leave the DNA, whereas TET1 associates stably. Overall, EPA directly regulates DNA methylation levels, permitting TET1 to exert its anti‐tumoral function.—Ceccarelli, V., Valentini, V., Ronchetti, S., Cannarile, L., Billi, M., Riccardi, C., Ottini, L., Talesa, V. N., Grignani, F., Vecchini, A. Eicosapentaenoic acid induces DNA demethylation in carcinoma cells through a TET1‐dependent mechanism. 32, 5990–6001 (2018). www.fasebj.org